Towards a rationale for technologies in adult education: some basic reflections on assumptions, implications and guidelines - Marescotti, Elena (Formazione & insegnamento, 2015)
This paper suggests some basic reflections in relation to interaction between ICT and the field of adult education, aimed at bring out elements of interest for a coherent rationale in the respect of capability, empowerment, participation and planning skills instances, which are attributable to adulthood. In fact, in the face of the pervasive needs for technological innovation, the educational perspective raises questions on required skills, not only instrumental, so that the role of technology is not reduced to quantitative aspects, even important, but it presses for a rethinking of educational experience quality. The results are a valorization of the “traditional” literacy, synergistically with digital ones, and, in particular, an underlining of the political implications, in the broad sense, for what concerns adult education.